ANALISIS PEMANFAATAN KECERDASAN BUATAN ARTIFICIAL INTELLIGENCE (AI) SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Nur Jihan, Adilla; Dina Nurkhakiki, Ade; Linas Ashari, Syifa’ul; Cahyono, Sapto; Naba’ul Insani, Auliya; Sulistyani, Anjar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology in the era of Society 5.0 has encouraged the education sector to adapt through the utilization of technology-based learning media, one of which is Artificial Intelligence (AI). However, the shift in learning paradigms from conventional to digital approaches often results in decreased student learning motivation if it is not accompanied by appropriate instructional strategies. This study aims to analyze the utilization of Artificial Intelligence as a learning medium in enhancing students’ learning motivation. The research method employed is a library research approach, examining various scientific journals, research articles, and academic sources relevant to the topics of AI and learning motivation. The data were analyzed using descriptive qualitative techniques through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the use of AI as a learning medium such as chatbots, educational games, instructional videos, interactive quizzes, and AI-based adaptive media positively contributes to improving students’ learning motivation across various educational levels. AI is able to create learning experiences that are more engaging, interactive, personalized, and aligned with learners’ needs, thereby increasing interest, active participation, and learning persistence. Therefore, Artificial Intelligence can be regarded as a relevant and effective innovation in learning media to support the enhancement of students’ learning motivation in the digital era.